2001
DOI: 10.1002/1522-2594(200102)45:2<191::aid-mrm1025>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion tensor measurements in myelin-deficient rat spinal cords

Abstract: The apparent diffusion tensor (ADT) was measured in excised and fixed spinal cords from myelin‐deficient (md) rats and age‐matched controls. These data were used to obtain the principal diffusivities of the ADT, and also the scalar invariant parameters D̄ (averaged principal diffusivity) and Aσ (anisotropy index) for four white matter and two gray matter regions. The results for white matter regions showed that the principal diffusivities were significantly higher for md animals, and while the D̄ was increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
155
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(169 citation statements)
references
References 33 publications
13
155
1
Order By: Relevance
“…The results in Table 2 show that the thickness of myelin significantly affects the predicted ADCs, in that with increasing myelin fraction the ADC is expected to decrease. The model is in qualitative agreement with the work by Gulani et al (22), who found in myelin-deficient rats the ADC in the spinal cord to be lower than in wildtype rats. These observations corroborate the importance of incorporating myelin in the simulation model.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results in Table 2 show that the thickness of myelin significantly affects the predicted ADCs, in that with increasing myelin fraction the ADC is expected to decrease. The model is in qualitative agreement with the work by Gulani et al (22), who found in myelin-deficient rats the ADC in the spinal cord to be lower than in wildtype rats. These observations corroborate the importance of incorporating myelin in the simulation model.…”
Section: Discussionsupporting
confidence: 91%
“…Most models applicable to biological systems such as axons rely on geometric approximations, such as square prisms (17), cylinders (11,20), and ellipsoids (18), and treated myelin sheaths as infinitesimally thin membranes. Although the MR signal contributed from myelin is minor (low water content and short T 2 relaxation time) and it was shown that the presence of the myelin sheath is not requisite for diffusion anisotropy (21)(22)(23), myelin nevertheless constitutes a significant proportion of white matter and, as mentioned, undergoes morphologic changes during injury and repair (12,13).…”
mentioning
confidence: 99%
“…A decrease in FA may be attributed to disorganized axons and hypomyelination. 33,34 Previous DTI studies of tuberous sclerosis complex also revealed a reduction of FA in the white matter lesions 12,13 and normal-appearing white matter. 14 The lower axial diffusivity in the tuberous sclerosis complex group suggested poor integrity of axons.…”
Section: Discussionmentioning
confidence: 94%
“…Diffusion anisotropy can be detected in the absence of myelin (Beaulieu, 2002), and the contribution of changes in myelin to altered diffusion measurements in vivo has been determined to be relatively low (Beaulieu, 2002, Beaulieu andAllen, 1994), with one study reporting a decrease of 20% in anisotropy in myelin-deficient animal models (Gulani et al, 2001). Nevertheless, in schizophrenia, myelination abnormalities have been demonstrated using MRI and T2 relaxation; reduced myelin water fraction was detected to a greater extent in the chronic than first episode groups and was localized to the genu of the corpus callosum and frontal WM (range 19-36%) (Flynn et al, 2003).…”
Section: Discussionmentioning
confidence: 99%